The Herd Behavior on Peer-To-Peer Online Lending Markets: Evidence from China - Rong Liu; Ningning Chen; Yuelei Li (Discrete Dynamics in Nature and Society)
Based on the transaction data and related borrowers’ characteristics of Renrendai.com, this study conducts an empirical study on the influencing factors of the investor’s herd behavior and rationality of herd behavior on a Chinese online lending platform. We mainly find that investors’ herd behavior exists significantly on Renrendai.com; there is an “inverted U-shaped” relationship between the number of bids and the herd behavior of investors. When the number of bids exceeds a certain amount, the time required for the order to obtain another bid will be prolonged, and the investors’ herd behavior will be slowed down; herd behavior on Renrendai.com in Chinese market is a partly rational pursuit, but irrational in general.